Precise Construction of Dual-Promising Anticancer Drugs Associated with Gold Nanomaterials on Glioma Cancer Cells - P. Baby Shakila; Abdurahman Hajinur Hirad; Abdullah A. Alarfaj; Samer Hasan Hussein-Al-Ali; Beza Mulugeta (Bioinorganic Chemistry and Applications)
Multiple chemodrugs with nanotechnology have proven to be an effective cancer treatment technique. When taken combined, cabazitaxel (CTX) and cisplatin (PT) have more excellent cytotoxic effects than drugs used alone in the chemotherapy of several different cancers. However, several severe side effects are associated with using these chemotherapy drugs in cancer patients. Gold nanomaterials (AuNMs) are promising as drug carriers because of their small diameter, easy surface modifications, good biocompatibility, and strong cell penetration. This work aimed to determine the CTX and PT encapsulated with AuNMs against human glioma U87 cancer cells. The fabrication of the AuNMs achieved a negative surface charge, polydispersity index, and the mean sizes. The combined cytotoxic effect of CTX and PT bound to AuNMs was greater than that of either drug alone when tested on U87 cells. The half inhibitory concentration (IC50) values for free PT were 54.7 μg/mL (at 24 h) and 4.8 g μg/mL (at 72 h). Results acquired from the MTT assay show cell growth decreases time- and concentration-dependent AuNMs, free CTX, free PT, and AuNMs@CTX/PT-induced cytotoxicity and, ultimately, the cell death of U87 cells via apoptosis. The biochemical apoptosis staining techniques investigated the cells’ morphological changes of the cells (acridine orange and ethidium bromide (AO-EB) and nuclear staining (DAPI) techniques). The AO-EB and nuclear staining results reveal that the NPs effectively killed cancer cells. Furthermore, the flow cytometry analysis examined the mode of cell death. Therefore, AuNMs@CTX/PT has excellent potential in the cancer therapy of different cancer cells.